Juridical Analysis Of The Rejection Of A Pretrial Motion Against The Order To Terminate Investigation (SP3) By The General Criminal Directorate Of The Lampung Regional Police (A Study of Decision No. 12/Pid.Pra/2025/PN Tjk) - Zainudin Hasan; Yohanes Merci (Cita konsultindo, 2026)
Pretrial proceedings provide legal protection against actions of law enforcement officials that are deemed to infringe upon the rights of suspects or other related parties during the investigation process. The research problems addressed are: how the mechanism of filing a pretrial motion against an SP3 and its implications for the legal rights of suspects and reporting parties in Decision No. 12/Pid.Pra/2025/PN Tjk; and whether the judge's considerations in rejecting the pretrial motion against the Order to Terminate Investigation (SP3) issued by the General Criminal Directorate of the Lampung Regional Police are in accordance with Decision No. 12/Pid.Pra/2025/PN Tjk. This study employs a normative juridical approach combined with an empirical approach, and draws conclusions using deductive reasoning to provide a general overview of the answers to the research problems based on the findings. The results indicate that the mechanism for filing a pretrial motion against an SP3 in Decision No. 12/Pid.Pra/2025/PN Tjk constitutes a form of judicial oversight over the investigator's authority to terminate an investigation. Through pretrial proceedings, the court assesses the validity of the SP3 from both formal and material aspects to prevent arbitrary actions and to ensure protection of the legal rights of suspects and reporting parties. Meanwhile, the judge's considerations in rejecting the pretrial motion are based on strict compliance with the provisions of the Criminal Procedure Code (KUHAP) and applicable legal procedures. The decision provides legal certainty for the suspect but limits the scope of legal remedies available to the reporting party. It is recommended that investigators place greater emphasis on prudence and accountability in issuing SP3s by basing such decisions on comprehensive and legally accountable analysis of evidence, as well as enhancing public understanding of pretrial proceedings as a means of legal protection. Judges are also expected not to focus solely on formal compliance with positive law, but to interpret the law proportionally while considering the sense of justice of all parties.